Neural Signatures of Working Memory in Age-related Hearing Loss. (1st March 2020) - Rosemann, Stephanie; Thiel, Christiane M.
Highlights: Intact neural signatures of working memory in mild to moderate hearing loss. Hard of hearing participants show decreased cognitive flexibility. Cognitive flexibility and hearing abilities predict speech-in-noise perception. Abstract: Age-related hearing loss affects the ability to hear high frequencies and therefore leads to difficulties in understanding speech, particularly under adverse listening conditions. This decrease in hearing can be partly compensated by the recruitment of executive functions, such as working memory. The compensatory effort may, however, lead to a decrease in available neural resources compromising cognitive abilities. We here aim to investigate whether mild to moderate hearing loss impacts prefrontal functions and related executive processes and whether these are related to speech-in-noise perception abilities. Nineteen hard of hearing and nineteen age-matched normal-hearing participants performed a working memory task to drive prefrontal activity, which was gauged with functional magnetic resonance imaging. In addition, speech-in-noise understanding, cognitive flexibility and inhibition control were assessed. Our results showed no differences in frontoparietal activation patterns and working memory performance between normal-hearing and hard of hearing participants. The behavioral assessment of further executive functions, however, provided evidence of lower cognitive flexibility in hard of hearing participants. Cognitive flexibility and hearing abilities further predicted speech-in-noise perception. We conclude that neural and behavioral signatures of working memory are intact in mild to moderate hearing loss. Moreover, cognitive flexibility seems to be closely related to hearing impairment and speech-in-noise perception and should, therefore, be investigated in future studies assessing age-related hearing loss and its implications on prefrontal functions.